Global health nursing in the 21st century - Breakey, Suellen; Corless, Inge B.; Meedzan, Nancy; Nicholas, Patrice K. (Springer Publishing Company, LLC, 2015)
The first book to present the successes, challenges, and opportunities of global health nursing This text is designed specifically for nurses and nursing students who have an interest in global health as a specialty, regardless of experience or education level. It reflects both the unique contributions of the nursing profession, and of other disciplines, which is in keeping with the Editors' perspective on how to bring about lasting change. The text views global health through a nursing lens, but maintains this awareness and appreciation of interprofessionalism throughout. The Editors and C.